Effect of acute hyperoxia on the bronchodilator response to salbutamol in stable asthmatic patients. - Dagg, K. D. (1996)
BACKGROUND: Recent animal studies have suggested that changes in oxygen tension may alter airway responses to bronchoconstrictor and bronchodilator stimuli. These effects may have relevance to the management of acute exacerbations of asthma but have not been well studied in man. This study was designed therefore to examine the effect of acute hyperoxia (Fio2 1.0) on the bronchodilator response to salbutamol in stable asthmatic patients. METHODS: Twelve stable adult asthmatic patients (three women) were studied using a randomised double blind placebo controlled crossover design. On two study days following baseline measurements patients breathed either air (Fio2 0.21) or oxygen (Fio2 1.0) for 10 minutes alone and then in combination with three incremental doses of nebulised salbutamol administered at 15 minute intervals. The same protocol was employed on two further study days using nebulised saline instead of salbutamol. RESULTS: The mean absolute change in forced expiratory volume in one second (FEV1) from baseline after salbutamol was similar on the normoxic and hyperoxic study days but significantly greater than the study days on which nebulised saline was administered. CONCLUSION: Acute hyperoxi does not potentiate the immediate bronchodilator response to salbutamol in stable asthmatic patients.